Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

Deposition distribution and optimization of a vertical three-zone counter-spraying device for greenhouse tomatoes - Zhongqing Sun; Yonghua Zhang; Liangchun Qi; Yumei Tang; Pei Wang; Zhenglin Liu; Linlin Yang; Xiuying Tang (Crop Protection, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Optimal grasping direction of a flexible gripper and its RGB-D multimodal estimation method - Jingwei Sun; Linlin Sun; Shuangxi Liu; Huawei Yang; Zixu Chen; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

A YjiC-like UDP-glycosyltransferase CtYjiC regulates melanization, infection-related development and virulence in Colletotrichum truncatum - Yulin Qian; Xiaoying Zhai; Qinyi Wang; Jun Liu; Linlin Zhang; Yaxin Zhang; Chunzhi Jin; Long Jin; Kee-Sun Shin; Qin Xiong (Physiological and Molecular Plant Pathology, 2026)

Comparative precipitation forecasting in the Northeastern Tibetan Plateau: Tree-ring reconstruction and future projections using machine learning and CMIP6 models - Longyun Ma; Haoyuan Xu; Jinjian Li; Zeyu Zheng; Linlin Cui; Caihong Liu; Shanlei Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A hierarchical Bayesian approach to estimate the most probable number (MPN) concentration of Salmonella in raw chicken from qualitative data - Tianmei Sun; Yangtai Liu; Yixuan Li; Linlin Xiao; Xiaojie Qin; Qingli Dong (International Journal of Food Microbiology, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

VHGAE: Drug-Target Interaction Prediction Model Based on Heterogeneous Graph Variational Autoencoder - Chen Zhang; Jiaqi Sun; Linlin Xing; Longbo Zhang; Hongzhen Cai; Kai Che (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Antibiotics and antibiotic resistance genes increase cyanobacterial blooms by altering microbial nitrogen transformations in water and sediment - Linlin Zhu; Tao Huang; Bo Wang; Lijun Zhou; Qingye Sun; Kaining Chen (Water Research, 2026)

Co-combustion of municipal solid waste and antibiotic fermentation residue: Gaseous pollutant emissions and ash slagging characteristics - Changhong Huang; Yuhang Du; Lei Bei; Jiaxing Du; Wu Yang; Ben Wang; Linlin Xu; Lushi Sun (Fuel, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

Gel-based fascia analogs from soy lipophilic protein and 11S globulin for connective tissue simulation in plant-based meat - Jiyuan Liu; Yixin Zhang; Linlin Liu; Ying Zhu; Yang Li; Mingshou Lv; Bingyu Sun; Xiuqing Zhu; Lianzhou Jiang; Yuyang Huang (Food Bioscience, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Exploring Co-occurrence Patterns of Macrobenthic Communities Across Intertidal and Offshore Zones in the Yellow River Delta, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2026)

Genesis of Successive Quasi-Linear Convective Systems over North China: Dynamical and Thermodynamic Forcing by a Cold Vortex, Complex Terrain, and Surface Boundaries - Yan Zhang; Rudi Xia; Jinfang Yin; Jianhua Sun; Linlin Zheng (Journal of Meteorological Research, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

NCAPG reprograms glycolytic and lipid metabolism by sustaining glycerophospholipid flux in small-cell lung cancer - Yang Sun; Jinglin Wen; Rui Su; Linlin Liu (Molecular and Cellular Biochemistry, 2026)

Identification of Fertility and Internal Genetic Uniformity in Monogerm Sugar Beet Hybrid Combinations - Chengwei Zhang; Rui Gao; Gaofei Lü; Zedong Wu; Linlin Sun (Sugar Tech, 2026)

Fouling and retention behavior of micro- and nano-plastics in gravity-driven membrane filtration - Xueying Chen; Dongwei Lu; Tongyu Li; Qingcan Zhou; Yinkun Sun; Linlin Zang; Jun Ma (Journal of Water Process Engineering, 2026)

Comparison of Turbulent Transport Dissimilarity and the Role of Coherent Structures in the Unstable Surface Layer Between Urban and Rural Areas - Qiyue Sun; Lu Zhang; Jiesheng Xue; Linlin Wang; Yubin Li; Yuanjian Yang (Boundary-Layer Meteorology, 2026)

Nanopore-Based Full-Length Transcriptome Sequencing: In-Depth Exploration of Green Sea Turtle (Chelonia mydas) Genome - Qi Huang; Yongjun Sun; Linlin Zhao; Wenbo Zhu; Fei Shao; Jin Xu; Yongjian Qin (Fishes, 2026)
The green sea turtle (Chelonia mydas), a widely distributed species, plays a crucial role in maintaining the marine ecosystem. However, studies on C. mydas require accurate and comprehensive genome annotation information. Long-read direct transcriptome data of C. mydas were obtained using direct RNA sequencing on the Oxford Nanopore Technologies (ONT) platform from blood tissue of a single captive individual. A total of 4061 novel transcripts were obtained by comparing long-read direct transcripts with genome annotation of C. mydas. We also predicted 2402 CDSs on the novel transcripts. Among them, 1208 (50.29%) had functional annotation information in the databases. In addition, we predicted and analyzed AS events, fusion transcripts, methylation sites, poly(A)s, and lncRNAs in the C. mydas long-read direct transcriptome. Overall, our study provides the a long-read direct blood transcriptome for C. mydas to complement and improve its genome annotation. This valuable resource will contribute to future research on C. mydas. Additionally, the analyses of transcriptome structure mentioned above may provide new insights and ideas for the study of C. mydas.

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Carbon dots/konjac glucomannan/starch anti-freezing gel: development and cryoprotective coating for beef preservation - Linlin Zhao; Zeyue Zhao; Wenqin Gu; Huinan Jiang; Hao Xu; Suqing Sun; Xiangren Meng (Food Research International, 2026)

Advances in the effect of the structure of high-moisture extruded plant-based meat on in vitro digestive properties - Yuyang Huang; Yixin Zhang; Yang Gao; Ying Zhu; Bingyu Sun; Linlin Liu; Jiyuan Liu; Baoning Zheng; Mingshou Lv; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

O2-supplementing photosensitizer AuNCs@TAT as a highly efficient NIR-II-controllable pyroptosis inducer for cancer photoimmunotherapy - Linlin Xie; Xingye Ma; Zheng Wang; Caifang Wang; Zhongxin Xiao; Ling-Dong Sun; Chun-Hua Yan; Chen-Jie Fang (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Two years in-situ phosphorus addition drives soil fungal network complexity and multifunctionality in a tropical cloud forest - Jinxiang Xiao; Linlin Lin; Ewuketu Linger; Wenxing Long; Yanfei Sun (Applied Soil Ecology, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Convection initiation over central–eastern China: Statistics show higher frequencies over mountains with less stringent atmospheric conditions and more heterogeneous surface characteristics - Qian Wei; Jianhua Sun; Xianhong Meng; Yuanchun Zhang; Linlin Zheng; Zheng Ma (Atmospheric Research, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Study on slow pyrolysis mechanism of non-metallic fractions in waste printed circuit boards using TG-FTIR-MS analysis - Lushi Sun; Gan Wan; Tao Chen; Jiaxing Du; Linlin Xu; Haitao Liu (Journal of Environmental Management, 2025)

Inhibitory effects of nisin and ε-polylysine on the microbial cell structure and physiological function of Bacillus amyloliquefaciens and applications in bread preservation - Min Qu; Xin Zhang; Xiuqing Zhu; Jingbo Kang; Linlin Liu; Mingshou Lv; Ying Zhu; Bingyu Sun (Food Bioscience, 2025)

A transformer-based deep learning approach for mechanical response prediction and failure analysis of precast bridge slab joints using strain field - Qiliang Zhao; Weijian Zhao; Linlin Yuan; Ruoshui Xing; Bochao Sun; Yuanzhang Yang (Engineering Structures, 2025)

Mitochondria-targeted nanoparticles with whole-course-repair efficacy in therapy of myocardial ischemia reperfusion injury - Xiya Wang; Hang Chen; Pingyuan Sun; Linlin Zhao; Renxiang Gui; Xu Wang; Emeli Chatterjee; Jiahong Xu; Jianle Chen; Xuerui Chen (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Identification for Fertility in Multigerm Sugar Beet Germplasm Resources of Molecular Markers - Jinghao Li; Linlin Sun; Zhi Pi; Shengnan Li; Zedong Wu (Sugar Tech, 2025)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

Remediation of alkaline cadmium (Cd) contaminated soil through biochar combined with organic fertilizer application - Linlin Liu; Jie Hu; Di Miao; Wenxin Yin; Wenping Sun; Lianglun Sun; Meizhen Tang (Environmental Geochemistry and Health, 2025)

The influence of different emulsifiers on dotted gizzard Shad (Konosirus punctatus) oil emulsions - Ying Guo; Linlin Wang; Kaiyi Wang; Li Li; Mengting Wei; Xin Wang; Zhen Wang; Baojie Jiang; Juanjuan Shao; Jilu Sun (Food Chemistry, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Effects of ultrasound on the structure and properties of soy protein gels prepared with different 11S/7S ratios - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Hydrocolloids, 2025)

Seismic performance of rubberized concrete double-column piers confined by corrugated steel tubes - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

Seismic behavior of prefabricated-assembled frames with corrugated steel tube confined connections and piers: Experiments, numerical models, and design - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Seasonal distribution patterns of P-cycling-related microbes and its association with internal phosphorus release in the eutrophic Lake Chaohu, China - Tingting Sun; Linlin Zhu; Tao Huang; Pengliang Tao; Yan Bao; Bo Wang; Qingye Sun; Kaining Chen (Journal of Environmental Sciences, 2025)

Mutual influence of bubble evolution and seepage flow in heterogeneous porous matrices - Linlin Gu; Shicai Sun; Rundong Zhang; Rongtao Yan; Yonghao Yin; Guanru Gong (Gas Science and Engineering, 2025)

Effect of cyanobacterial bloom proliferation on antibiotic resistance genes in the sediments of a eutrophic lake - Bo Wang; Tao Huang; Linlin Zhu; Jiawei Hu; Shaodong Ma; Qingye Sun; Kaining Chen (Environmental Research, 2025)

Engineering efficient and stable CsPbBr3 perovskite nanocrystals via multi-functional molecular mediated surface strategy toward white light-emitting devices - Hanyun Yang; Haoqi Zhu; Linlin Ma; Mengwei Luo; Hang Guo; Lepeng Zhou; Wenxu Sun; Bin Xue; Lei Zhang (Chemical Engineering Journal, 2025)

Occupational exposure to amorphous silica nanoparticles alters lung function and metabolomic features - Xuemin Shi; Chen Liang; LinLin Wang; Xuefeng Bai; Ruiyang Ding; Zhiwei Sun (Toxicology Letters, 2025)

One-step narrow-thermal-cycling strand exchange amplification for sensitive detection of porcine reproductive and respiratory syndrome virus - Linlin Zhuang; Chunlei Song; Li Sun; Haiqiang Xie; Liqun Wang; Qingxin Liu; Hongjing Shi; Jianbo Yang; Qiuping Shen (Archives of Microbiology, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Licorice water extract improves constipation by repairing the intestinal barrier and regulating the gut microbiota: A potential alternative treatment strategy - Mingwei Sun; Meng Zhao; Linlin Du; Jieying Hou; Juane Dong; Bin Zhang (Food Bioscience, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

Hydrological Connectivity Induces Changes in Macrobenthos Functional Feeding Groups in a Typical Tidal Creek System of the Yellow River Delta - Qinglu Fu; Li Chen; Debin Sun; Jiao Wang; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

The influence of different drying methods on the molecular structure and digestive resistance of type 3 resistant starch (RS3) - Qing Su; Linlin Sun; Lirong Chen; Xingya Wang; Kaichang Liu; Kuijie Gong (Food Chemistry, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Understanding the effect and mechanism of ε-polylysine on the improvement of tofu storage quality via biofilm inhibition by Bacillus licheniformis and Bacillus amyloliquefaciens - Jingbo Kang; Xin Zhang; Yuyang Huang; Ying Zhu; Linlin Liu; Bingyu Sun; Min Qu; Xiuqing Zhu (Food Bioscience, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

The dewatering performance and mechanism of streptomycin mycelial residue based on Fenton oxidation - Linlin Xu; Xingxing Zhou; Jiaxing Du; Gan Wan; Lushi Sun (Process Safety and Environmental Protection, 2025)

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Effect of freezing-thawing treatment on the quality and structure of soymilk gels induced by different coagulants - Ying Zhu; Wenhua Lei; Lidan Qiu; Simiao Liu; Ruqi Guo; Yuyang Huang; Linlin Liu; Mingshou Lv; Bingyu Sun; Min Qu; Ying Sun; Xiuqing Zhu (Food Hydrocolloids, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

Effect of freeze-thaw cycles on the quality of Yuba with different protein-lipid ratios on its protein-lipid network system - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Chemistry, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Distribution, transport and ecological risk prediction of organophosphate esters in China seas based on machine learning - Rui Chen; Wenyang Huang; Linlin Sun; Jingyan Yang; Tiantian Ma; Rongguang Shi (Science of The Total Environment, 2024)

A comparative study on the toxic effects of lead pollution and nanoplastic-lead mixed pollution on red drum and their detoxification strategies - Zhicheng Sun; Linlin Zhao; Xin Peng; Bin Kang (Journal of Hazardous Materials, 2024)

Evaluation of Tembusu virus single-round infectious particle as vaccine vector in chickens - Yunzhen Huang; Zhe Liu; Junqin Zhang; Jiawen Dong; Linlin Li; Yong Xiang; Ruihuan Kuang; Shimin Gao; Minhua Sun; Yongjie Liu (Veterinary Microbiology, 2024)

Artificial river flow regulation triggered spatio-temporal changes in marine macrobenthos of the Yellow River Estuary - Debin Sun; Jiao Wang; Qinglu Fu; Linlin Chen; Jing Chen; Teng Sun; Baoquan Li (Marine Environmental Research, 2024)

Molecular epidemiological investigation of Salmonella isolated from the environment, animals, foods and patients in China - Linlin Xiao; Xiaojie Qin; Hu Xiao; Yuehua Gao; Tanmei Sun; Xiaolu Dong; Yulin Long; Xuejuan Xia; Zhuosi Li; Xiang Wang; Qingli Dong (Food Research International, 2024)

Rational design of pulse-electrolysis protocols promotes molten-salt electrorefining - Leyang Li; Ruiyang Sun; Rui Yuan; Manpeng Lin; Linlin Wang; Qi Wang; Jiguo Tu; Handong Jiao; Shuqiang Jiao (Chemical Engineering Journal, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

Turnover structures in macrobenthic communities rather than nestedness in the Yellow River Delta wetland, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Aquatic Sciences, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

A multi-omics-based investigation into the regulation of phenolics in fresh maize kernels at different developmental stages - Xiaomin Tian; Di Han; Linlin Sun; Yuqiu Guo; Kaichang Liu; Lirong Chen; Kuijie Gong (Journal of Cereal Science, 2024)

Elemental mercury removal by copper-containing brominated pyrolytic chars derived from waste printed circuit boards - Gan Wan; Tao Chen; Linlin Xu; Lushi Sun (Fuel, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

Extraction of organic solvents and preferential recovery of lithium from spent lithium-ion batteries by in-situ carbothermal reduction - Jian Zou; Ruihan Zhang; Yali Zhang; Linlin Chen; Yaoguo Huang; Xianfu Sun (Process Safety and Environmental Protection, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

Experimental and theoretical studies on effective synergistic low-temperature removal of NO and typical volatile organic compounds (VOCs) from flue gas based on Cu@VWTi catalyst - Siyuan Lei; Lele Wang; Linlin Xu; Ben Wang; Lushi Sun (Journal of Cleaner Production, 2024)

Role of microalgae-bacterial consortium in wastewater treatment: A review - Lixin Li; Wei Chai; Caiyu Sun; Linlin Huang; Tao Sheng; Zhiwei Song; Fang Ma (Journal of Environmental Management, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Formation mechanism of polycyclic aromatic hydrocarbons during mineral oil pyrolysis: A ReaxFF molecular dynamics study - Linlin Xu; Gan Wan; Lushi Sun; Li Lin (Fuel, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Machine learning reveals the selection pressure exerted by nonantibiotic pharmaceuticals at environmentally relevant concentrations on antibiotic resistance genotypes - Shaojing Sun; Yan Sun; Jialu Geng; Linlin Geng; Fan Meng; Qing Wang; Hong Qi (Journal of Environmental Management, 2024)

Changes of microbial residues over century-long soil development after tidal flat reclamation in eastern China - Dezhi Yan; Weiyue Sun; Linlin Ye; Bo Liu (CATENA, 2024)

Applying bio-oxidation waste solution into two-stage oxidation process to enhance the bio-oxidation of pyrite: Insight on enhanced mechanism - Shiqi Zhang; Hongying Yang; Linlin Tong; Pengcheng Ma; Zuochun Luan; Qifei Sun (Journal of Water Process Engineering, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Kinetics and debromination studies on the pyrolysis of waste printed circuit boards with the addition of copper and copper oxides - Tao Chen; Chuan Ma; Ben Wang; Linlin Xu; Wu Yang; Lushi Sun (Journal of Cleaner Production, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

Seismic behavior of embedded rubberized concrete-filled corrugated steel tube column-to-foundation connections: Experimental, numerical modelling, and design - Mingyang Feng; Baodong Liu; Linlin Zhang; Yaoyao Wang; Haibo Sun (Soil Dynamics and Earthquake Engineering, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Advancing ocean subsurface thermal structure estimation in the Pacific Ocean: A multi-model ensemble machine learning approach - Jifeng Qi; Linlin Zhang; Baoshu Yin; Delei Li; Bowen Xie; Guimin Sun (Dynamics of Atmospheres and Oceans, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Analysis of mRNA and MicroRNA Expression Profiles of Nervous Tissues and Reproductive Tissues in Male Procambarus clarkii After Silencing IAG - Rong Sun; Shaokui Yi; Linlin Shi; Kianann Tan; Ruixue Shi; Siqi Yang; Yanhe Li (Marine Biotechnology, 2023)

Establishment of ultrasensitive immunoassay strip based on colloidal gold-McAb probe for detecting cyproheptadine hydrochloride and six phenothiazines in feed - Xiaofei Hu; Guanqiong Na; Yaning Sun; Yunrui Xing; Linlin Chen; Zhang Gaiping (Food Additives & Contaminants: Part A, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

Reaction pathways control of long-chain alkanes hydroisomerization and hydrocracking via tailoring the metal-acid sites intimacy - Wenli Zhao; Linlin Liu; Xiaopo Niu; Xinyue Yang; Jiuyi Sun; Qingfa Wang (Fuel, 2023)

Effect of Na+ and Ca2+ on the texture, structure and microstructure of composite protein gel of mung bean protein and wheat gluten - Ruqi Guo; Linlin Liu; Yuyang Huang; Mingshou Lv; Ying Zhu; Zihan Wang; Xiuqing Zhu; Bingyu Sun (Food Research International, 2023)

The effects of selenium on the growth and bone development in the weaned rats - Hongan Li; Linlin Jia; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Bioscience, 2023)

Novel electron donor boosting the electron supply capacity of hierarchical structure carbon nitride for efficient photocatalytic hydrogen peroxide production - Linlin Sun; Xiaoshuo Liu; Huiling Ji; Xunlei Ding; Nan Jiang; Jigang Wang (Chemical Engineering Journal, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Exploring the therapeutic mechanism of Banxia Xiexin Decoction in mild cognitive impairment and diabetes mellitus: a network pharmacology approach - Cong Li; Wei Yang; Yubo Meng; Lina Feng; Linlin Sun; Zhenghong Li; Xingfang Liu; Mingquan Li (Metabolic Brain Disease, 2023)

Construction of a novel ferrihydrite/MoS2 heterogeneous Fenton-like catalyst for efficient degradation of organic pollutants under neutral conditions - Da Chang; Juanjuan Sun; Chang Wang; Linlin Hao; Ming Zeng (Environmental Science and Pollution Research, 2023)

Quadristerols A−G: Seven undescribed ergosterols from Aspergillus quadrilineata - Mengsha Wei; Xiaoxin Li; Hong Liao; Linlin Liu; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

On the effects of rheological behavior on landslide motion and tsunami hazard for the Baiyun Slide in the South China Sea - Zhiyuan Ren; Hua Liu; Linlin Li; Yuchen Wang; Qiliang Sun (Landslides, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Effect of bubbles on the gas–water migration during gas hydrate dissociation by depressurization - Shicai Sun; Zhendong Yang; Linlin Gu; Haifei Lin; Changxing Zhang (Fuel, 2023)

Citrate-enhanced leaching of arsenic from coal with simulated flue gas under UV irradiation - Shun Qiu; Zhenzhen Lu; Wenshou Sun; Linlin Tao; Jin Li; Jintong Li (Chemical Engineering Journal, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Global analysis of gene expression profiles and gout symptoms in goslings infected with goose astrovirus - Chenggang Liu; Linlin Li; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Yong Xiang; Jin Jin; Xianshe Huang; Gang Wang; Minhua Sun; Ming Liao (Veterinary Microbiology, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Bimetal Cu and Fe modified g-C3N4 sheets grown on carbon skeleton for efficient and selective photocatalytic reduction of CO2 to CO - Songyuan Bian; Xueyan Li; Long Zhang; Libin Wang; Jingzhen Wang; Qing Xu; Linlin Zang; Yanhong Zhang; Liguo Sun (Journal of Environmental Chemical Engineering, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

UV-B regulates seasonal greening of albino leaves by modulating CsHY5-inhibiting chlorophyll biosynthesis in Camellia sinensis cv. Huangkui - Xuyang Liu; Xin Cheng; Jingjie Cao; Wenfeng Zhu; Ying Sun; Ning Lin; Xiaochun Wan; Linlin Liu (Plant Science, 2023)

High Fischer ratio peptide of hemp seed: Preparation and anti-fatigue evaluation in vivo and in vitro - Zhu Ying; Huang Yuyang; Li Meiying; Sun Bingyu; Liu Linlin; Lv Mingshou; Qu Min; Guan Huanan; Zhu Xiuqing (Food Research International, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Correction to: Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2023)

Convolutional neural networks (CNNs)-based multi-category damage detection and recognition of high-speed rail (HSR) reinforced concrete (RC) bridges using test images - Lingkun Chen; Wenxin Chen; Lu Wang; Chencheng Zhai; Xiaolun Hu; Linlin Sun; Yuan Tian; Xiaoming Huang; Lizhong Jiang (Engineering Structures, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

H2O2-TiO2 photocatalytic degradation of chondroitin sulfate and in vivo absorption and excertion of its product - Weigong Tian; Ying You; Xiaona Sun; Linlin Wang; Lilong Wang; Songtao Wang; Chunqing Ai; Shuang Song (Carbohydrate Polymers, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Development of effective expanded vermiculite flocculant for enhanced primary treatment of swine wastewater: Lab-scale investigations - Linlin Hao; Juanjuan Sun; Ming Zeng; Chang Wang (Applied Clay Science, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Two-stage chemical-biological oxidation process for low-grade refractory gold concentrate with high arsenic and sulfur - Shiqi Zhang; Hongying Yang; Linlin Tong; Pengcheng Ma; Zuochun Luan; Qifei Sun; Youqin Zhou (Minerals Engineering, 2023)

Gas hydrate dissociation by depressurization along with ice occurrence and sand migration - Shicai Sun; Linlin Gu; Zhendong Yang; Haifei Lin; Changxing Zhang (Gas Science and Engineering, 2023)

Pahs emission characteristics and the mitigation in the valuable products from used mineral oil thermolysis recycling - Linlin Xu; Jie Yu; Gan Wan; Lushi Sun (Fuel, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Fluoride-Induced Sperm Damage and HuR-Mediated Excessive Apoptosis and Autophagy in Spermatocytes - Yanyan Li; Jianbin Zhang; Linlin Sun; Hongyu Zhao; Xiaohan Jia; Yingri Zhang; Yuanbin Li (Biological Trace Element Research, 2023)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2022)

Identification and functional analysis of two GJA8 variants in Chinese families with eye anomalies - Linlin Zhou; Xuejiao Sun; Xinyao Wang; Kangyu Liu; Zilin Zhong; Jianjun Chen (Molecular Genetics and Genomics, 2022)

Identification and Characterization of the Homeobox Gene Family in Fusarium pseudograminearum Reveal Their Roles in Pathogenicity - Yuming Ma; Jingya Zhao; Wenbo Chen; Xuejing Geng; Tianli He; Shengli Ding; Bingjian Sun; Honglian Li; Linlin Chen (Biochemical Genetics, 2022)

Estimating the impacts of climate change on the habitat suitability of common minke whales integrating local adaptation - Bin Sun; Linlin Zhao; Fei Shao; Zhichuang Lu; Jiashen Tian; Changdong Liu (Frontiers in Marine Science, 2022)
Climate change is exerting unprecedented effects on the habitats of marine mammals. Common minke whales ( Balaenoptera acutorostrata ) have suffered immense harm from commercial whaling, and the recovery of this species is likely threatened by climate change. To better manage and conserve this species, it is important to predict its current habitat distribution and the potential change under future climate change scenarios. Such predictions are typically generated by species distribution models (SDMs), which construct a correlation between species occurrence data and its habitat environmental variables. SDMs are commonly constructed at the species level, assuming a homogenous response of the species to climatic variables across their entire geographic range. Spatially segregated populations from the same species inhabit distinct environments and gradually adapt to the local conditions, resulting in niche differentiation among populations. Species-level SDMs that ignore the effects of local adaptation mask differences in population responses to climate change and might present an unrealistic picture of potential species distributions. Based on morphological and genetic evidence, the common minke whale was divided into three populations: the North Atlantic population (NAP), Southern Hemisphere population (SHP) and North Pacific population (NPP); these populations inhabit isolated geographic areas with distinct environmental conditions. We quantified the realized niches of these populations and found evidence of significant ecological niche differentiation. We then constructed SDMs at the species and population levels and compared the predictions from these two types of models under different climate change scenarios. Both types of models projected similar change trends in species range, with a contraction of future suitable habitats for the NAP and SHP and an expansion for the NPP. However, the magnitudes of this change differed; the population-level model projected more optimistic results for the SHP and NAP, indicating less habitat loss. This study highlighted the importance of considering local adaptation when estimating the impact of climate change on species habitat suitability. These spatiotemporal predictions provide essential knowledge for designing climate-adaptive conservation and management strategies, such as the delimitation of mobile marine protected areas (MPAs).

Extensive Interspecific Gene Flow Shaped Complex Evolutionary History and Underestimated Species Diversity in Rapidly Radiated Dolphins - Weijian Guo; Di Sun; Yang Cao; Linlin Xiao; Xin Huang; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Mammalian Evolution, 2022)
Recently diverged taxa are often characterized by high rates of hybridization, which can complicate phylogenetic reconstruction. For this reason, the phylogenetic relationships and evolutionary history of dolphins are still not very well resolved; the question of whether the genera Tursiops and Stenella are monophyletic is especially controversial. Here, we performed re-sequencing of six dolphin genomes and combined them with eight previously published dolphin SRA datasets and six whole-genome datasets to investigate the phylogenetic relationships of dolphins and test the monophyly hypothesis of Tursiops and Stenella . Phylogenetic reconstruction with the maximum likelihood and Bayesian methods of concatenated loci, as well as with coalescence analyses of sliding window trees, produced a concordant and well-supported tree. Our studies support the non-monophyletic status of Tursiops and Stenella because the species referred these genera do not form exclusive monophyletic clades. This suggests that the current taxonomy of both genera might not reflect their evolutionary history and may underestimate their diversity. A four-taxon D -statistic (ABBA-BABA) test, five-taxon D FOIL test, and tree-based PhyloNet analyses all showed extensive gene flow across dolphin species, which could explain the instability in resolving phylogenetic relationship of oceanic dolphins with different and limited markers . This study could be a good case to demonstrate how genomic data can reveal complex speciation and phylogeny in rapidly radiating animal groups.

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Functional Trait Responses of Macrobenthos to Anthropogenic Pressure in Three Temperate Intertidal Communities - Jian-Yu Dong; Linlin Zhao; Xiaolong Yang; Xin Sun; Xiumei Zhang (Frontiers in Marine Science, 2021)
With the increasing impact of human activities on marine ecosystems, there is a growing need to assess how the components of marine ecosystems (e.g., macrobenthos) respond to these anthropogenic pressures. In this work, the trait-based approach was used to assess the effects of anthropogenic pressures represented by the area of land-based aquaculture pond (Pond Area) and heavy metals on the macrobenthic communities in three intertidal zones[Aoshan Bay (AO), Wenquan River and Daren River (RW), and Xiaodao Bay (XD)] of Laoshan Bay, Shandong Peninsula, China. Compared with RW and XD, AO was under more pressure in terms of the average concentrations of heavy metals and total organic carbon (TOC) in sediments and also in the Pond Area. Fuzzy correspondence analysis (FCA) showed that there were significant differences in the composition of functional traits among the three regions (PERMANOVA; p < 0.05). In the highly polluted area, macrobenthic communities exhibited a combination of traits, such as relatively short life span, weak mobility, feeding on deposits, and more tolerant to organic matter, whereas in a less polluted area, they exhibited a combination of traits, such as relatively long life span, relatively high mobility, and more sensitivity to organic matter. The RDA results showed that the distribution of the trait modalities was significantly affected by heavy metals (Hg and Cd), TOC, Pond Area, and sampled location. Variation partitioning analysis (VPA) indicated that the shared influence of sediment-related pollution factors and Pond Area contributed most to the variance of the functional traits, which implied that human activities directly and/or indirectly lead to changes in functional traits of macrobenthic communities in the intertidal zones.

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

Metabolism and antioxidation regulation of total flavanones from Sedum sarmentosum Bunge against high-fat diet-induced fatty liver disease in Nile tilapia (Oreochromis niloticus) - Kai Yu; Kai Huang; Zhanyang Tang; Xiuyun Huang; Linlin Sun; Linxing Pang; Cuiqin Mo (Fish Physiology and Biochemistry, 2021)

Effects of sodium arsenite and dimethyl arsenic acid on Liaoning cashmere goat skin fibroblasts - Fengqin Zhao; Chuang Wang; Dongyu Sun; Linlin Zhang; Zhiyue Wang; Jun Piao; Jingai Piao; Mei Jin (Environmental Science and Pollution Research, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Comparison of Class 2 Integron Integrase Activities - Xiaotong Wang; Nana Kong; Mei Cao; Long Zhang; Muzhen Sun; Linlin Xiao; Gang Li; Quhao Wei (Current Microbiology, 2021)

Colloidal gold-based immunochromatographic strip assay for the rapid detection of diminazene in milk - Linlin Chen; Yaning Sun; Xiaofei Hu; Yunrui Xing; Sharon Kwee; Guanqiong Na; Gaiping Zhang (Food Additives & Contaminants: Part A, 2020)

Streptomyces albicerus sp. nov., a novel actinomycete isolated from the sediments of the Tailan River in Xinjiang, China - Beibei Sun; Linlin Yuan; Zhanfeng Xia; Chuanxing Wan; Lili Zhang (Archives of Microbiology, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Tissue distribution of transcription for 29 lipid metabolism-related genes in Takifugu rubripes, a marine teleost storing lipid predominantly in liver - Houguo Xu; Xiaoxue Meng; Linlin Jia; Yuliang Wei; Bo Sun; Mengqing Liang (Fish Physiology and Biochemistry, 2020)

Evaluation and spatiotemporal characteristics of glacier service value in the Qilian Mountains - Meiping Sun; Weiqian Ma; Xiaojun Yao; Linlin Zhao; Zhongqin Li; Dahe Qin (Journal of Geographical Sciences, 2020)

An Improved Coal Permeability Model with Variable Cleat Width and Klinkenberg Coefficient - Gang Wang; Zhiyong Xiao; Junhong Yu; Lu Zhang; Linlin Sun (Geotechnical and Geological Engineering, 2020)

Cloning and Characterization of Cholesterol 25-Hydroxylase (ch25h) From a Marine Teleost, Chinese Tongue Sole (Cynoglossus semilaevis), and Its Gene Expressions in Response to Dietary Arachidonic Acid - Houguo Xu; Bo Sun; Linlin Jia; Yuliang Wei; Zhangbin Liao; Mengqing Liang (Frontiers in Marine Science, 2020)

Identification of Fusarium graminearum-responsive miRNAs and their targets in wheat by sRNA sequencing and degradome analysis - Xiaojie Jin; Linlin Jia; Yongxia Wang; Baoquan Li; Dongfa Sun; Xueyan Chen (Functional & Integrative Genomics, 2020)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Diversity of the Fusarium pathogens associated with crown rot in the Huanghuai wheat‐growing region of China - Haifeng Zhou; Xiaolun He; Shuo Wang; Qingzhou Ma; Bingjian Sun; Shengli Ding; Linlin Chen; Meng Zhang; Honglian Li (Environmental Microbiology, 2019)
Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensis was isolated from the disease specimens and tested for virulence to wheat. The result of the pathogenicity revealed that an intraspecific differentiation existed in F. pseudograminearum ; sequence analysis of the EF‐1α gene showed that 194 F. pseudograminearum isolates were differentiated into two distinct clades which closed to the strains from Australia and China respectively, but neither pathogenicity nor EF‐1α sequence was related to the geographic origins of these isolates. However, universal rice primers‐polymerase chain reaction showed a correlation with the geographical origins of the 194 isolates, which were divided into eight subclusters, the level of genetic diversity was higher within a geographical population than among the different populations. The results of these analyses can be directly used to facilitate disease monitoring and development of control strategies.

Geochemical characteristics of dust aerosol availability in northwestern China - Xunming Wang; Jimin Sun; Mingrui Qiang; Caixia Zhang; Danfeng Li; Ting Hua; Hui Li; Lili Lang; Linlin Jiao; Diwen Cai; Wenyong Ma (Arabian Journal of Geosciences, 2019)

Reclamation suitability evaluation of damaged mined land based on the integrated index method and the difference-product method - Linlin Cheng; Haiyuan Sun (Environmental Science and Pollution Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

Plastic Mulch and Plant Density Influencing Soil Water Content and Yield of Rainfed Maize in North‐Eastern China - Shijun Sun; Zhijun Chen; Hao Jiang; Xudong Zhang; Linlin Zhang; Daocai Chi (Irrigation and Drainage, 2019)
Plastic mulch, in combination with high plant density, is a common practice for rainfed maize production in north‐eastern China. However, the influence of these practices on soil water storage, maize yield and maize water productivity in different precipitation years is not well understood. In this paper, a 3‐year split‐plot field experiment was designed to compare non‐mulching and plastic film mulching in maize at 67 500 and 82 500 plants per ha in 2013, 2014 and 2015, and also 97 500 plants per ha in 2014 and 2015. Results revealed an increasing trend of precipitation in the study area from 1962 to 2015 and that the number of dry years and extreme years (including extreme dry and wet years) was increasing. In the moderately wet year 2013 and the moderately dry year 2015, the combination of 82 500 plants per ha and plastic film mulching produced the highest yield and water productivity (8.2 t ha −1 , 1.7 kg m −3 and 8.3 t ha −1 , 2.3 kg m −3 , respectively) for maize, while in the extremely dry year 2014 the highest yield (5.6 t ha −1 ) occurred with 97 500 plants per ha and non‐mulching. This research might be helpful for smallholder farmers needing optimal agricultural strategies to improve maize production in rainfed areas of north‐east China. © 2018 John Wiley & Sons, Ltd.

Relative trajectory-driven virtual dynamic occlusal adjustment for dental restorations - Sukun Tian; Ning Dai; Xiaosheng Cheng; Linlin Li; Yuchun Sun; Haihua Cui (Medical & Biological Engineering & Computing, 2019)

Effects of artificial aeration and iron inputs on the transformation of carbon and phosphorus in a typical wetland soil - Linlin Zhang; Ze Tang; Sijian Zhang; Xueying Jia; Xiaofei Yu; Guangzhi Sun; Yuanchun Zou (Journal of Soils and Sediments, 2018)

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Macropores regulate CO2 behavior in an andisol soil - Linlin Guo; Taku Nishimura; Hiromi Imoto; Zhigang Sun (Paddy and Water Environment, 2018)

Fermentation Kinetics of Enzymatic Hydrolysis Bagasse Solutions for Producing l-Lactic Acid - Yuanyuan Cui; Rong Liu; Linlin Xu; Wenjing Zheng; Weidong Sun (Sugar Tech, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

Definition and classification system of glacial lake for inventory and hazards study - Xiaojun Yao; Shiyin Liu; Lei Han; Meiping Sun; Linlin Zhao (Journal of Geographical Sciences, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

Identification of forty-five gene-derived polymorphic microsatellite loci for the sea cucumber, Apostichopus japonicus - MENG CHEN; LINLIN GAO; WEIJIE ZHANG; HONGZHENG YOU; QIAN SUN; YAQING CHANG (Journal of Genetics, 2016)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

Association of interleukin-6 gene polymorphism with coronary artery disease: an updated systematic review and cumulative meta-analysis - Haifeng Hou; Chenglin Wang; Fengjing Sun; Linlin Zhao; Aishe Dun; Zheng Sun (Inflammation Research, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Expression of tomato SlTIP2;2 enhances the tolerance to salt stress in the transgenic Arabidopsis and interacts with target proteins - Shichao Xin; Guohong Yu; Linlin Sun; Xiaojing Qiang; Na Xu; Xianguo Cheng (Journal of Plant Research, 2014)

Overexpression of the PLAP-1 gene inhibits the differentiation of BMSCs into osteoblast-like cells - Jing Sun; Ting Zhang; Panpan Zhang; Linlin Lv; Yanzhi Wang; Jing Zhang; Shu Li (Journal of Molecular Histology, 2014)

Mesoaccumbens dopamine signaling alteration underlies behavioral transition from tolerance to sensitization to morphine rewarding properties during morphine withdrawal - Linlin Sun; Ling Hu; Yijing Li; Cailian Cui (Brain Structure and Function, 2014)

Erratum to: Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Reducing basal salicylic acid enhances Arabidopsis tolerance to lead or cadmium - Siyuan Tao; Lihong Sun; Chunyan Ma; Linlin Li; Guangzhe Li; Lin Hao (Plant and Soil, 2013)

Rhizobacteria (Pseudomonas sp. SB) assist phytoremediation of oily-sludge-contaminated soil by tall fescue (Testuca arundinacea L.) - Wuxing Liu; Jianying Sun; Linlin Ding; Yongming Luo; Mengfang Chen; Caixian Tang (Plant and Soil, 2013)

Life cycle assessment of composite packaging waste management—a Chinese case study on aseptic packaging - Minghui Xie; Qi Qiao; Qihong Sun; Linlin Zhang (The International Journal of Life Cycle Assessment, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Identification and genomic analysis of two duck-origin Tembusu virus strains in southern China - Linlin Li; Hejia An; Minhua Sun; Jiawen Dong; Jianfeng Yuan; Qilin Hu (Virus Genes, 2012)

Elements in Lung Tissues of Patients from a High Lung Cancer Incidence Area of China - Linlin Zhang; Jungang Lv; Shengkun Sun (Biological Trace Element Research, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

Application of ATOVS radiance-bias correction to typhoon track prediction with Ensemble Kalman Filter data assimilation - Limei Cui; Jianhua Sun; Linlin Qi; Ting Lei (Advances in Atmospheric Sciences, 2011)

A Critical Role of Src-Suppressed C Kinase Substrate in Rat Astrocytes After Chronic Constriction Injury - Yinyin Xia; Haiou Liu; Aiguo Shen; Yonghua Liu; Linlin Sun; Tao Tao; Qing Ke; Chun Cheng (NeuroMolecular Medicine, 2010)

Isolation of two novel complete Ty1-copia retrotransposons from apple and demonstration of use of derived S-SAP markers for distinguishing bud sports of Malus domestica cv. Fuji - Guiling Zhao; Hongyan Dai; Linlin Chang; Yue Ma; Haiyue Sun; Ping He; Zhihong Zhang (Tree Genetics & Genomes, 2010)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

Increased expression of CDK11p58 and cyclin D3 following spinal cord injury in rats - Yuhong Ji; Feng Xiao; Linlin Sun; Jing Qin; Shuxian Shi; Junling Yang; Yonghua Liu; Dan Zhou; Jian Zhao; Aiguo Shen (Molecular and Cellular Biochemistry, 2008)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)

Application of ATOVS microwave radiance assimilation to rainfall prediction in Summer 2004 - Linlin Qi; Jianhua Sun (Advances in Atmospheric Sciences, 2006)

An analysis of a meso-β system in a mei-yu front using the intensive observation data during CHeRES 2002 - Sun Jianhua; Zhang Xiaoling; Qi Linlin; Zhao Sixiong (Advances in Atmospheric Sciences, 2005)